Physiology of the blood system. Methodological instructions for laboratory classes of subject «Animal physiology» for foreign students of the speciality 221 «Veterinary medicine», branch of knowledge 21 «Veterinary Medicine» - Kolomiiets Iryna (ЛНУВМ та БТ імені С. З. Ґжицького, 2022)
In the methodological instructions are represented the main experiments of the chapter «Physiology of the blood system», handout for foreign students, which correspond to the syllabus of the educational discipline «Animal Physiology» for foreign students of the speciality 221 «Veterinary medicine», branch of knowledge 21 «Veterinary Medicine». They contain also list of questions for current and summary (examination) knowledge control. They include a list of methodological and recommended literature. The methodological instructions will be also useful for foreign students of medical and biological high schools.
Keywords: фізіологія системи крові; кров